Estructura del ingreso y estrategias de subsistencia de la familia rural en la Zona Cetro del Estado de Yucatán - Samuel Alvarado Yah; Carlos E. Leyva Morales; Rafael Bolio Domínguez (Colegio de Economistas de A Coru\~na, 2007)
– The purpose of this article was to study the relationship between the level of education, income and job opportunities for families in rural areas in the center of Yucatán, Mexico. For this reason, a conglomerate sample was carried out and its results were analyzed using different economic theories. We proved the connection between the level of education and the type of jobs held by family members in the subject area. Results showed that there are problems in both the content and the goals of the educational system, as well as education is not broadly encouraged. The level of education that individuals have is closely related to the income they earn. However, there are problems concerning qualitative and quantitative aspects in this relationship (net income and purchasing power). For this reason, the relationships analyzed are not definite, since education is not the only causal element and does not entirely determine the job market and salaries inside and outside these communities.
Keywords: 330; Bildungsniveau; Haushaltseinkommen; Arbeitsplatz; Landbevölkerung; Yucatán